ANALISIS KANDUNGAN FORMALIN PADA IKAN ASIN KEPALA BATU YANG BERADA DI PASAR TRADISIONAL KOTA JAMBI - Intan Lestari; Gebi Sangra Pratiwi; Yuliawati (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2022)
Formalin or formaldehyde belongs to a group of strong disinfectant compounds that are often used as corpse preservatives, but can also be used food preservatives and additives, formalin can damage the body if consumed in excess. This research aims to find out the content of formalin in The Stone Head Salted Fish located in the Traditional Market of Jambi City. The study used a UV-Vis spectrophotometer measured at wavelengths of 400-600 nm. Based on the results obtained from 25 samples of Salted Fish Head stone analyzed, taken from traditional markets namely market A, Market B, Market C, Market D and Market E, which obtained formalin levels in each market vary with the highest value in mama market, with a rate of 1.0327μg/mg. In the sample of Salted Fish Head Stone circulating in the traditional market of Jambi City, it protects formalin.